Chapter L'Arno al tempo di Leonardo, fra geomorfologia e geografia storica: un'analisi diacronica - Salvi, Tania (Territori, 2023)
The chapter offers a methodology to reconstruct the structure of the Arno course, between Empoli and the mouth, at the beginning of the 16th century. Various documentary deposits have been used: analysis of geological information, to define the palaeochannels structure; historical sources; post-Leonardian historical cartography and a stratified bibliography to create information for geo-referencing Leonardo's documents. This is compared with Leonardo's drawings (Windsor and Madrid), ca. 1503-1504, offers an unprecedented picture of the territorial structure of the river.